PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN KITAB FIKIH KLASIK DI MAN 2 PALEMBANG - Noni Juli Astuti; Muhammad Win Afgani; Fajri Ismail (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This research is entitled "Learning of Islamic Religious Education with the Book of Classical Jurisprudence at MAN 2 Palembang". The main issues of the research discussed in this thesis are: (1) How is the learning plan for Islamic religious education with classical fiqh books at MAN 2 Palembang, (2) What is the learning process for Islamic religious education with classical fiqh books at MAN 2 Palembang, (3) ) How to evaluate the learning of Islamic religious education with classical fiqh books at MAN 2 Palembang. This type of research is descriptive qualitative research location in MAN 2 Palembang. Data collection methods used are observation, interviews and documentation. The data analysis technique is descriptive qualitative analysis, namely data reduction, presentation, and drawing conclusions. The results of the study showed that learning Islamic religious education with classical fiqh books at MAN 2 Palembang was optimal. This can be seen from good planning, process and evaluation.